Navigating migraine chronicity: the role of environmental risk factors and triggers - Doğan, Hasan; Piri Cinar, Bilge; Iyilikci, Osman; Uluduz, Ezgi; Eyüpoglu, Sevim; Iskender, Mustafa; Kadioglu, Ummugulsum; Uluduz, Derya; Özge, Aynur (Frontiers in Neurology, 2025)
PurposeMigraine is a prevalent and debilitating neurological condition that can significantly impact an individual’s quality of life. While various genetic and environmental factors contribute to the development and chronification of migraine, the role of specific environmental factors in the chronification of this condition remains inadequately explored. This article aims to address this research gap by focusing on the impact of manageable and unmanageable factors on the chronicity of migraine.Patients and methodsThis cross-sectional observational study included 498 patients diagnosed with episodic or chronic migraine. Demographic characteristics of the patients were recorded on the demographic data form. Then, the patient’s headache characteristics (duration, type, presence of aura, accompanying features, etc.) and the answers to the questions about possible triggers of migraine and environmental factors were recorded in the data form.ResultsIn the chronic migraine group, oversleeping and stress were reported as triggers at a higher rate than in the episodic migraine group. In the episodic migraine group, it was found that participants who had TV transmitters were significantly less likely to benefit from treatment, while in the chronic migraine group, it was found that participants who had pets were significantly less likely to benefit from treatment.ConclusionThis study sheds light on the intricate relationship between environmental factors, migraine phenotype, and treatment response. By using comprehensive statistical methods and analyzing a rich dataset, we have gained valuable insights into the complexities of migraine management.